1993
DOI: 10.1002/j.1460-2075.1993.tb05960.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyprotein processing in African swine fever virus: a novel gene expression strategy for a DNA virus.

Abstract: This report shows that African swine fever virus (ASFV)‐‐a large DNA‐containing virus‐‐synthesizes a polyprotein to produce several of its structural proteins. By immunoprecipitation analysis, we have found that ASFV polyprotein is a 220 kDa myristoylated polypeptide (pp220) which, after proteolytic processing, gives rise to four major structural proteins: p150, p37, p34 and p14. Processing of the ASFV polyprotein takes place at the consensus sequence Gly‐Gly‐X and occurs through an ordered cascade of proteoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(107 citation statements)
references
References 47 publications
3
102
0
Order By: Relevance
“…During ASFV infection, polyprotein pp220 is firstly cleaved at the Gly-Gly-Gly sequence at positions 43-45 and the Gly-Gly-Ala sequence at positions 892-894 to give rise to the mature product p150 and the intermediate precursor protein pp90 (6) (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During ASFV infection, polyprotein pp220 is firstly cleaved at the Gly-Gly-Gly sequence at positions 43-45 and the Gly-Gly-Ala sequence at positions 892-894 to give rise to the mature product p150 and the intermediate precursor protein pp90 (6) (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…This antibody, as well as the rabbit polyclonal anti-p150, anti-p34, and anti-p37/p14 sera, which also recognize polyprotein pp220, have been previously characterized (6,8,25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex virus particle is formed by proteins in excess of 50, including those with structural functions and enzymes packaged for use early in infection. Genes encoding 15 of the structural proteins have been characterized, with two of these encoding polyproteins that are processed into four and two virion proteins each (Simon-Mateo et al, 1993,1997Andres et al, 2001).…”
Section: Proteinsmentioning
confidence: 99%
“…This result suggested strongly that a low M r protein is also encoded by the 5' end of the previously reported gene. In accordance with this hypothesis, a protein of M r 14000 has been found to be derived from a large precursor that gives rise to several ASFV proteins which become incorporated into virions, including p37, after proteolytic cleavage at a Gly-Gly-X sequence (Simdn-Mateo et al, 1993). The sequence of the two clones of group C showed that they expressed an ORF known to encode a polypeptide of approximate Mr 15 000, present in the virus particle (L. Martinez & E. Vifiuela, unpublished results).…”
Section: Mapping and Sequence Of Orf A137rmentioning
confidence: 68%